Naringenin and β-carotene convert human white adipocytes to a beige phenotype and elevate hormone- stimulated lipolysis - Coulter, Ann A.; Greenway, Frank L.; Zhang, Dachuan; Ghosh, Sujoy; Coulter, Cathryn R.; James, Sarah L.; He, Yanlin; Cusimano, Luke A.; Rebello, Candida J. (Frontiers in Endocrinology, 2023)
Naringenin, a peroxisome proliferator-activated receptor (PPAR) activator found in citrus fruits, upregulates markers of thermogenesis and insulin sensitivity in human adipose tissue. Our pharmacokinetics clinical trial demonstrated that naringenin is safe and bioavailable, and our case report showed that naringenin causes weight loss and improves insulin sensitivity. PPARs form heterodimers with retinoic-X-receptors (RXRs) at promoter elements of target genes. Retinoic acid is an RXR ligand metabolized from dietary carotenoids. The carotenoid β-carotene reduces adiposity and insulin resistance in clinical trials. Our goal was to examine if carotenoids strengthen the beneficial effects of naringenin on human adipocyte metabolism. Human preadipocytes from donors with obesity were differentiated in culture and treated with 8µM naringenin + 2µM β-carotene (NRBC) for seven days. Candidate genes involved in lipolysis, thermogenesis, and glucose metabolism were measured using qRT-PCR and immunoblotting. We found that carotenoids act synergistically with naringenin to boost UCP1 and glucose metabolism genes including GLUT4 and adiponectin, compared to naringenin alone. Protein levels of PPARα, PPARγ and PPARγ-coactivator-1ɑ, key modulators of thermogenesis and insulin sensitivity, were also upregulated after treatment with NRBC. Transcriptome sequencing was conducted and the bioinformatics analyses of the data revealed that NRBC induced enzymes for several non-UCP1 pathways for energy expenditure including triglyceride cycling, creatine kinases, and Peptidase M20 Domain Containing 1 (PM20D1). A comprehensive analysis of changes in receptor expression showed that NRBC upregulated eight receptors that have been linked to lipolysis or thermogenesis including the β1-adrenergic receptor and the parathyroid hormone receptor. Lipolysis fuels thermogenesis, and NRBC increased levels of triglyceride lipases and agonist-stimulated lipolysis in adipocytes. We observed that expression of RXRγ, an isoform of unknown function, was induced ten-fold after treatment with NRBC. We show that RXRγ is a coactivator bound to the immunoprecipitated PPARγ protein complex from white and beige human adipocytes. In conclusion, NRBC upregulates the capacity for lipolysis and expression of key enzymatic pathways for thermogenesis in human adipocytes and has therapeutic potential.